Leader power and interpersonal conflict: the mediating effects of management communication style in government link companies, Malaysia / Rozilah Abdul Aziz - Abdul Aziz, Rozilah (2018)
In a complex and fast-changing business environment, it is evidenced that managers are faced with multitudes of problems in the organizational setting. One of the never ending problems faced by managers is interpersonal conflict that occurs between individuals or groups in organizations that emphasizes the interaction of human factors in an organization. In order to circumvent conflicts that transpire among the employees, most organizations have emphasized on effective communication that are most likely to improve the employee own chances to survive and prosper in organizations. Review of related international literatures revealed the importance of communication style in decision making, nevertheless, there is lack of empirical evidence to support this in the Malaysian context and this study contributes deeper understanding of some of the critical aspects of management communication style. Using a research framework constructed from adaptation of two key power models: Lusch Model (1976) and Richmond, McCroskey, Davis and Koontz’s Theory (1980), this study explores the argument that management communication style (tell, sell, consult and join) interpersonal conflict (task conflict and relationship conflict) are influenced by leader power (referent, coercive, expert, legitimate and referent). In particular, this study seeks to investigate the mediating effects of management communication style on the relationship between leader power an interpersonal conflict. Thus, it presents and discusses empirical findings from data collected from 388 executives working directly under HR Managers in GLCs, Malaysia applying Structural Equation Modeling (AMOS Version 20) and Statistical Package or Social Science (SPSS Version 20). The data was analyzed adopting two-step model-building approach of SEM – Measurement Model and Structural Model. Findings of this study indicated that Leader Power support he mediating role of management communication style which indicates a final model with acceptable level of GFI = 0.900, CFI = 0.986 , TLI = 0.984, and RMSEA = 0.024. The overall re-specified measurement model was found to be adequately fit. This study represents a more accurate methodological process, attempting to clearly define the constructs of leader power, management communication style and interpersonal conflict. Assessments of the reliabilities and validities of each construct using Confirmatory Factor Analysis (CFA) strengthened the correspondence rules between both empirical and theoretical concept. Results of this study signify that Human Resource Managers must consider how strategic effective communication helps the supervisor-subordinates to make a quality decisions by minimizing the conflicts that transpired during the process of making decisions. Hence, management should discover effective communication strategies that can be applied to minimize the degree of interpersonal conflict that transpires during the decision making process. Finally, there is also a necessity for the managers to understand the impact of decision making has on the organizations and know what style is being used so supervisors-subordinates know how to communicate with one another in ensuring the quality of decision-making process is successful with zero conflict. In short, this research helped to produce a segment in a more inclusive global picture of the antecedents and outcomes of Management Communication Style of a leader.